2000
DOI: 10.1046/j.1439-0418.2000.00413.x
|View full text |Cite
|
Sign up to set email alerts
|

Enumerative sampling plans for grasshopper egg pods in northern Benin

Abstract: The spatial distributions of egg pods of two grasshopper species, Hieroglyphus daganensis Krauss and Cataloipus fuscocoeruleipes Sjöstedt, collected from three oviposition sites, Piliostigma thonningi (Schumach.) Milne‐Redhead, Vetiveria nigritana (L.) and Sorghum bicolor (L.) Moench, are described using Taylor's power law. Both grasshopper species showed a highly aggregated distribution with Taylor's index of dispersion ranging between 1.380 and 1.709, except for C. fuscocoeruleipes from S. bicolor where an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…DeÞning an acceptable level of precision is necessarily subjective. We chose the rather liberal standard of D Յ 0.3, which has been used previously in cropping scenarios where a reasonably coarse characterization of the pest population density was acceptable (Barney and Legg 1988, Hutchinson et al 1988, Garat et al 1999, Shah et al 2000, Dawson et al 2006. To place this in context, a value of 0.25 enables detection of a halving or doubling of the sample mean (Southwood and Henderson 2000).…”
Section: Methodsmentioning
confidence: 99%
“…DeÞning an acceptable level of precision is necessarily subjective. We chose the rather liberal standard of D Յ 0.3, which has been used previously in cropping scenarios where a reasonably coarse characterization of the pest population density was acceptable (Barney and Legg 1988, Hutchinson et al 1988, Garat et al 1999, Shah et al 2000, Dawson et al 2006. To place this in context, a value of 0.25 enables detection of a halving or doubling of the sample mean (Southwood and Henderson 2000).…”
Section: Methodsmentioning
confidence: 99%
“…where SD is the standard deviation in sample estimate of m x ðÞand n is the number (n) of sampling units collected (Kuno 1969;Waters et al 2009). Normally, D ¼ 0:3i s used as a standard for the fixed level of precision (Barney and Legg 1988;Hutchison et al 1988;Garat et al 1999;Shah et al 2000;Waters et al 2009). The minimum sample size required to estimate density is given by the formula (Kuno 1969):…”
Section: Application Of Regression Through the Origin In Sequential Smentioning
confidence: 99%
“…Dry season surveys carried out by crop protection services can detect areas where there are high egg-pod concentrations. Shah et al (2000) proposed a sampling method to assess eggpod densities with a relatively high degree of accuracy. Monitoring between March and June would be diffi cult since this is the period when farmers are involved in preparing their fi elds for the next cropping season.…”
Section: Monitoring and Control Strategiesmentioning
confidence: 99%
“…Th e only period possible for such assessments would be from December to February. Modder (1986) and Shah et al (2000) suggested fi nancially compensating farmers in order to get enough people involved in these survey operations. Rapidly locating areas with suitable rainfall conditions at the onset of the monsoon season on the basis of fi eld and remote-sensing data could enhance control of just-hatched nymphs (Burt et al 1995(Burt et al , 1997.…”
Section: Monitoring and Control Strategiesmentioning
confidence: 99%